2019
DOI: 10.14455/isec.res.2019.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bamboo Fibers and Limestone Powder on Fresh Properties of Self-Compacting Concrete

Abstract: Self-compacting concrete (SCC) flows through densely steel reinforced elements and consolidates under self-weight without need for vibration or compaction. This helps in complex and densely reinforced structures. The integration of fibers and fillers in concrete improves its general properties. The addition of fibers in particular can regulate the flow and workability of the concrete; hence, the high workable nature of SCC can be an ideal mix for the incorporation of fibers. This research investigates the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…From the obtained results, it can be seen that Limestone leads to an increase in flow time of V-funnel while the effect of MP is inconspicuous in this case. This can be explained by the effect of limestone on the enhancement of viscosity, as a result of its contribution in modifying the grading of the solid particles in mixture suspension and modified the water quantity available for the hydration process (Ede et al, 2019;Youness et al, 2020). Similar results were also reported by other researchers (Benabed et al, 2012;Babikir and Ahmed, 2020;Daoud and Mahgoub, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…From the obtained results, it can be seen that Limestone leads to an increase in flow time of V-funnel while the effect of MP is inconspicuous in this case. This can be explained by the effect of limestone on the enhancement of viscosity, as a result of its contribution in modifying the grading of the solid particles in mixture suspension and modified the water quantity available for the hydration process (Ede et al, 2019;Youness et al, 2020). Similar results were also reported by other researchers (Benabed et al, 2012;Babikir and Ahmed, 2020;Daoud and Mahgoub, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there is a high demand for props and scaffolds for the construction of various types of structures and the maintenance of existing ones (Ede, et al, 2018). This was observed to be a result of the increased construction of buildings with multiple floors.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, the use of bamboo in construction in Nigeria is still based on the fabricator's creativity, since there are no authorities in its uses and consequent construction framework for the trade. Thus, the structural collapse of floor slabs during construction has been attributed to the use of bamboo (Ede et al, 2018). Despite this, Bamboo still appears to be the most commonly used material compared to steel and timber for scaffoldings and props in recent times in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Archila, Kaminski, Trujillo, Escamilla, and Harries (2018) cautioned on the use of bamboo as reinforced material in concrete in place of steel; however, Adom-Asamoah, Osei, and Afrifa (2018) in their study suggested the use of bamboo reinforced SCC mix for rural construction. Meanwhile, incorporation of bamboo as fiber in a self-compacting concrete-enhanced mechanical behaviour of the SCC and possibly ensuring the production of environmentally friendly and durable concrete with better crack resistance and reduced maintenance cost (Ede et al, 2019). According to Bashir, Gupta, Abubakr, and Abba (2018) that bamboo fiber can be used to enhance the compressive strength of concrete, however, reported a decrease in the flexure as the amount of the fiber content increases.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been carried out on the use of natural fiber in SCC with supplementary cementitious material such as limestone, fly ash, silica fume, improving its workability using admixtures (Adhavanathan, 2017;Amirtharaj, 2017). A recent study by Mounir, Mohammed, Zeinab, and Kasem (2014); Oshogbunu (2018) and Ede et al (2019) mentioned that there are very few studies on the use of combining bamboo fiber and limestone as filler materials in the production of sustainable self-compacting concrete. A study by Dewi, Wijaya, and Christin Remayanti (2017) recommended the use of 40 g of bamboo fiber as the optimum content in a concrete mix for the control of crack and improving the quality of the concrete.…”
Section: Introductionmentioning
confidence: 99%